An Assessment on Bird’s Diversity in Bagmati River Corridor - Thapa, Saroj; Paudel, Shambhu; BK, Dipak (The Initiation, 2010)
Bagmati River is considered as a potential conservation area in terms of the bio-diversity conservation due to its unique and diversified habitat distribution. Due to various causes, the river is being polluted and hence habitat degradation rate is increasing. As a consequence, the direct effect is seen on birds inhabiting there. Aiming the assessment of bird's diversity, one year survey was conducted in Bagmati River from Tilganga Bridge to chobhar Gorge Bridge (here after termed as Bagmati river corridor) by applying the point count method .In the total enumeration, 100 of birds species were recorded among which 7 are listed in CITES appendix. The bird species that are regarded as globally threatened are not recorded in the study area. In this report, some potential patches in the study area, are described as hot spots, considering the higher probability of recording maximum number of birds species. The public voice is also collected to find out the public perception on the present status of birds of Bagmati river corridor using the questionaire method. Some causes of habitat destruction and some potential conservation measures are also mentioned. Key Words: Bagmati river corridor, Birds, Conservation, Hotspots, Diversity, Habitat DOI: 10.3126/init.v2i1.2520 The Initiation Vol.2(1) 2008 pp34-40